Brief Solution Focused Therapy in Ukraine to Work with People with Emotional, Cognitive and Behavioural Disorders - Levus, Nadiia; Hupalovska, Viktoriia; Salamon , Oleh; Yurkiv, Yuliya (Journal of Education Culture and Society, 2022)
Aim. To study the way how Brief Solution Focused Therapy (BSFT) tackles emotional, cognitive and behavioural disorders. To provide basic definitions of such disorders and identify major approaches and techniques focusing on Brief Solution Focused Therapy aspects that may be applied in psychotherapeutic works with these people.Methods. Ana\lysis and synthesis of scientific data regarding defining emotional, cognitive and behavioural disorders. Distinguishing basic diagnostic signs of such disorders in clients. Methods of BSFT psychotherapy.Results. The following BSFT techniques proved to be the most effective in the work on emotional disorders: problem-free talk, compliments, resource questions and scaling. These techniques can be called the most emotional ones – the techniques that call for your emotions, replenish your psychological resource, help rebuild your emotional attitude to the situation, look at it from a different angle. BSFT-based psycho-correction and psychotherapy of cognitive impairments and behavioural disorders is longer and more fundamental. Effective techniques are goal setting, resource identification, and also there are special turning points, such as the technique of life analysis, which is a variant of scaling as a method, use of coping questions.Conclusions. BSFT-methods are effective in addressing different disorders – both partial (emotional, behavioural, cognitive) and more complex ones. The fact that BSFT does not focus on the negative emotional conditions, the problem and its causes, enables the depressive clients, grieving clients and clients experiencing loss to relatively fast discover their resources and start building plans, demonstrating how it is possible to optimize the process of overcoming complicated life situations.